PATOFISIOLOGI BIOMOLEKULAR NEUROPATI DIABETES - Shahdevi Nandar Kurniawan (NEURONA, 2012)
DIABETES IS A CHRONIC DISEASE THAT IS COMMON IN ALMOST ALL COUNTRIES THE DEATH RATE FROM DIABETES WAS 39 MILLION PEOPLE WORLDWIDE IN 2010 AND REMAINS A MAJOR PROBLEM IN EACH COUNTRY APPROXIMATELY 60 TO 70 OF PEOPLE WITH DIABETES HAVE MILD TO SEVERE FORMS OF NERVOUS SYSTEM DAMAGE MORE THAN HALF OF ALL INDIVIDUALS WITH DIABETES SUFFER NEUROPATHY WITH RISK OF AMPUTATION OF ONE OR MORE OF THE LOWER LIMB IS ESTIMATED TO REACH 15 THE DEFINITION OF DISTAL SYMMETRIC DIABETIC POLYNEUROPATHY DPN IS THE INTERNATIONALLY AGREED SYMPTOMS ANDOR SIGNS OF PERIPHERAL NERVE DYSFUNCTION IN DIABETES PATIENT AFTER EXCLUSION OF OTHER CAUSES CONFIRMATION OF DIAGNOSIS IS DONE BY QUANTITATIVE ELECTROPHYSIOLOGICAL TESTING OF MOTOR SENSORY AND AUTONOMIC FUNCTIONS